Public participation, regulatory compliance and green development in China based on provincial panel data. (1st September 2019) - Fu, Jingyan; Geng, Yanyun
Abstract: Since China entered the 'new normal', China has begun to aim at high-quality green development. Therefore, the government proposes building an environmental governance system that is government-led, is enterprises-oriented, and includes the participation of social organizations and the public in multi-governance and source prevention. China must implement the concept of green development and jointly promote the construction of ecological civilization. However, there is no scholarly research on the impact of pluralistic governance on green development. Based on this information, this paper will use the panel data of China's 30 provinces from 2004 to 2014. This paper divides green development into the green development modes and the green development effect, and we study the impact of public participation and regulation compliance on green development. The results show that: (1) the improvement of corporate regulatory compliance is conducive to improving the green development mode and promoting the green development effect; and is thus conducive to achieving green development. (2) Different means of public participation have different effects on green development. (3) The interactive effect of corporate regulation compliance and public participation can promote the improvement of green technology and improve the green effect. That is, public participation can guide enterprises to improve compliance and promote green development. (4) The degree of public participation has a positive effect on the improvement of the green development mode in the eastern and central regions, and it has an obvious effect on the green development effect in the western region.